Aspect-Based Sentiment Analysis In The Asean Tourism Sector: A Systematic Literature Review - Jovi Arnandy; Indra Budi; Amanah Ramadiah; Prabu Kresna Putra; Aris Budi Santoso (Jurnal Impresi Indonesia, 2025)
Online reviews are becoming increasingly important for assessing tourist satisfaction, and although aspect-based sentiment analysis (ABSA) can offer in-depth insights, its use in the ASEAN tourism sector is still largely unexamined. Problem: This gap highlights a significant research issue, as there is insufficient knowledge re-garding the present condition, obstacles, and particular possibilities for applying advanced sentiment analysis methods in this distinctive, multicultural area . Objectives: The main aim of this study is to methodically identify worldwide research trends, highlight gaps, and describe the challenges of utilizing ABSA in the tour-ism industry, concentrating on their effects on ASEAN . Methods Used: To accomplish this, a systematic literature review (SLR) was performed on 61 chosen articles following the PRISMA methodology. Re-sults: The findings indicate a notable research gap marked by a narrow emphasis on the ASEAN region and the application of less sophisticated methods in current studies; the main challenges recognized include the varie-ty of languages, cultural differences, and a lack of datasets in local languages . Conclusion & Solution Offered: This organized review of literature concludes by providing suggestions for a plan-based approach that allows the region to use online reviews to improve its tourism competitiveness, emphasizing the necessity of creating local data resources, encouraging cooperation among different fields, and using data-driven tools to support small businesses .